Speaking Through Personality: A Qualitative Analysis of Introvert and Extrovert Learners in Efl Classroom - Nurul Ramadhani Putri Amril; Eny Syatriana; Sulkifli (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study explores how introverted and extroverted learners’ speaking performance reflects their learning styles in an EFL classroom and how they interact during speaking activities at SMP Negeri 2 Sungguminasa. Using a descriptive qualitative design, six eighth-grade students (three introverts and three extroverts) were selected through purposive sampling based on classroom observations and teacher recommendations. Data were collected through non-participant classroom observations, audio/video recordings, and semi-structured interviews, then analyzed using Miles, Huberman, and Saldaña’s interactive model of data condensation, data display, and conclusion drawing. Findings show that introverted students display a reflective learning style, preferring to prepare in quiet settings, memorise at home, listen more, and take 3–5 second pauses before responding, using silence as internal rehearsal to prioritise accuracy. In contrast, extroverted students demonstrate a social/experiential learning style, characterised by quick and spontaneous responses, frequent hand-raising, initiating discussions, and treating every speaking opportunity as “learning by doing” to build fluency. Classroom interaction patterns indicate that extroverts tend to drive and sustain discussion, while introverts contribute more selectively with well-structured answers once they feel ready. These results suggest that personality differences do not determine speaking success, but shape distinct learning routes toward speaking proficiency. The study recommends that EFL teachers design inclusive speaking activities that provide planning time and quiet preparation for introverts, alongside interactive and spontaneous tasks that support extroverts’ social learning preferences.